An Analysis of Teachers’ Strategies in Teaching English in Inclusive Classrooms at SMP Pembangunan Laboratorium UNP - Zurnisasi, Zurnisasi; Fitrawati, Fitrawati (Journal of English Language Teaching, 2025)
This study investigates the teaching strategies used by an English teacher in an inclusive classroom and the problems encountered during their implementation at SMP Pembangunan Laboratorium UNP. Inclusive education ensures equal learning opportunities for all students regardless of abilities or backgrounds. This was a qualitative descriptive approach with a case study method. This study focused on one English teacher teaching class 8B, the most diverse class in the school. Data were collected through three classroom observations, a semi-structured interview, and supporting documentation such as field notes and photographs. The findings revealed that the teacher employed various strategies, including direct instruction, expository learning, differentiated instruction, peer tutoring, and discovery learning with mind mapping.      The choice of strategies depended on classroom conditions and student engagement levels. Despite the teacher’s adaptability, several problems emerged, such as difficulty preparing suitable materials, students’ limited comprehension of instructions, lack of inclusive education training, unexpected behaviors from students with autism, and insufficient parental support. To address these challenges, the teacher utilized self-learning, discussions with colleagues and the principal, and creative problem-solving. This study underscores the importance of teacher adaptability and institutional support in inclusive classrooms, offering insights for improving inclusive English teaching practices in junior high schools in Indonesia.